Efecto del tiempo de infusión y relación cascarilla de cacao-pulpa de pitahaya en la evaluación fisicoquímica y sensorial de una bebida - Moreira Macías, Inés Marisela (2022)
The present study evaluated the effect of infusion time and cocoa husk-pitahaya pulp ratio on the physicochemical and sensory evaluation of a beverage. A completely randomized design was used in a factorial arrangement of A*B with 6 treatments and 3 replications. The treatments were obtained from the relationship of the factors: A: Ratio of cocoa husks and pitahaya pulp and B: Cocoa husk infusion time. The experimental unit consisted of 1 kg of the drink, formulated with 0.2% xanthan gum; 0.35% citric acid and 10% sugar as experimental material, which was pasteurized, packed in glass containers and stored at a temperature of 4 °C. Physicochemical parameters (soluble solids, pH and titratable acidity) and functional parameters (antioxidant capacity and total polyphenols) were evaluated. For total polyphenols, the best treatment was T5 (50% infusion of fine aroma cocoa husk and 39.45% pitahaya pulp/20 minutes) with a value of 35.60 (mg GAE/g) and in antioxidant capacity it was T1 (70% infusion of fine aroma cocoa husk and 19.45% pitahaya pulp/20 minutes) with a value of 175.57 (µMOL Trolox/g). For sensory analysis, a tasting test was carried out where the variables were evaluated: smell, color and flavor were statistically the same in all treatments, which is why it is defined that the treatments do not differ from each other, it was possible to establish that there was no significant difference between the treatments.